2018
DOI: 10.1016/j.pharep.2018.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy induced by cardamonin is associated with mTORC1 inhibition in SKOV3 cells

Abstract: These findings demonstrated that the autophagy induced by cardamonin was associated with mTORC1 inhibition through decreasing the protein level of Raptor in SKOV3 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…We have investigated the antiproliferation effect of cardamonin in various cancer cells. It demonstrated that the efficiency-concentration ranged from 5 μM to 30 μM [ 13 , 15 , 16 ]. In the present study, the inhibitory effect of cardamonin (5, 10 and 20 μM) on the lactate secretion was measured in SKOV3 cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have investigated the antiproliferation effect of cardamonin in various cancer cells. It demonstrated that the efficiency-concentration ranged from 5 μM to 30 μM [ 13 , 15 , 16 ]. In the present study, the inhibitory effect of cardamonin (5, 10 and 20 μM) on the lactate secretion was measured in SKOV3 cells.…”
Section: Methodsmentioning
confidence: 99%
“…Cardamonin inhibits the proliferation and metastasis of various cancer cells [ 13 15 ]. In our previous studies, we demonstrate that the antitumor effect of cardamonin dependents on mTOR inhibition [ 16 , 17 ]. Recently, we find that the autophagy induction is account for the antiproliferative activity of cardamonin [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…mTORC2 also stimulates serum and glucocorticoid-regulated kinase 1 (SGK1), a kinase that contributes to the regulation of glucose and creatine transporters, hormone release, inflammation, growth and apoptosis [57], belongs to the AGC family of protein kinases [54] and is involved in aberrant cell growth, survival and invasiveness. Nevertheless, recent findings have highlighted how mTORC2 could also act as a repressor of chaperone-mediated autophagy [58,59], which is frequently deregulated in numerous age-related disorders [60,61]. Moreover, mTORC2 increases Na + transport and regulates cell migration [62,63].…”
Section: Activity Of Mtor Complexmentioning
confidence: 99%
“…The interaction of RAPTOR and SHOC2 has been shown to inhibit RAPTOR‐mTOR binding and induce autophagy via inactivating mTORC1, which facilitates, in parallel, RAS‐ERK activation and PDAC progression . Autophagy induced by cardamonin is associated with mTORC1 inhibition through decreasing RAPTOR in cervical cancer . Moreover, RAPTOR upregulation has been shown to contribute to PI3K‐mTOR inhibitor resistance in renal cancer, further indicating the effect of RAPTOR on mTORC1 during tumor progression and outcomes.…”
Section: Introductionmentioning
confidence: 96%
“…12 Autophagy induced by cardamonin is associated with mTORC1 inhibition through decreasing RAPTOR in cervical cancer. 13 Moreover, RAPTOR upregulation has been shown to contribute to PI3K-mTOR inhibitor resistance in renal cancer, 14 further indicating the effect of RAPTOR on mTORC1 during tumor progression and outcomes. Therefore, RAPTOR might be a favorable molecule to target in order to solve the issue of mTORC1-targeted preparations in tumor treatment.…”
Section: Introductionmentioning
confidence: 99%